2000
DOI: 10.1128/aac.44.5.1153-1158.2000
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Trovafloxacin and Ampicillin-Sulbactam Alone or in Combination versus Three Strains of Vancomycin- Intermediate Staphylococcus aureus in an In Vitro Pharmacodynamic Infection Model

Abstract: The recent isolation of clinical strains of methicillin-resistant Staphylococcus aureus (MRSA) with intermediate susceptibility (MICs, 8 g/ml) to vancomycin (vancomycin-intermediate S. aureus [VISA]) emphasizes the importance of developing novel antimicrobial regimens and/or agents for future treatment. We studied the activities of ampicillin-sulbactam and trovafloxacin alone or in combination against three unique strains of VISA in an in vitro infection model. Two VISA strains were trovafloxacin susceptible (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…The time-killing methods also showed an additional synergistic effect with the addition of sulbactam to the combination of cephalosporin and daptomycin. Although previous studies [31][32][33] have shown a synergistic effect of sulbactam in various combinations, such as arbekacin with ampicillin-sulbactam, ours is the first to report a synergistic effect of daptomycin and cephalosporins with sulbactam against daptomycin-nonsusceptible VISA/h-VISA.…”
Section: Discussioncontrasting
confidence: 48%
“…The time-killing methods also showed an additional synergistic effect with the addition of sulbactam to the combination of cephalosporin and daptomycin. Although previous studies [31][32][33] have shown a synergistic effect of sulbactam in various combinations, such as arbekacin with ampicillin-sulbactam, ours is the first to report a synergistic effect of daptomycin and cephalosporins with sulbactam against daptomycin-nonsusceptible VISA/h-VISA.…”
Section: Discussioncontrasting
confidence: 48%
“…[1] where α is the first-order elimination rate constant of the distribution phase (α phase), β is the first-order elimination rate constant of the elimination phase (β phase), and A and B are the zero-time intercepts for the α and β phases, respectively. To simulate the drug concentration-time profile described by equation [1], circuit A ( Fig. 2) was devised by being based on the elementary circuits (i) and (ii) ( Fig.…”
Section: In Vitro Pharmacokinetic Model Of IV Bolus Injectionmentioning
confidence: 99%
“…when tϾT d (i.e., after the drip infusion), [7] where the above parameters are the same as in equation [1], except that dosing is finished at T d .…”
Section: C(t)ϭae ϫαT ϩBe ϫβTmentioning
confidence: 99%